Analysis of the American Worker : Full-time and Part-time Wage Differentials - Hines, Zach (My University, 2011)
A fundamental question in labor economics is the degree to which full time workers get paid more than part time workers after adjusting for other major factors. This study will compare wages between white men and white women, ages 25-55, using U.S. data from the 2006-07 census.
Color poster with text, charts, and graphs.
Keywords: Labor economics; Hours of labor--United States; Wages--United States; Posters; Wages--United States--Sex differences